Comparative proteomics of nearisogenic maize inbred lines to identify potential aflatoxinresistance markers - Brown, R.L.; Menkir, A.; Bandyopadhyay, Ranajit; Cleveland, T.E.; Chen, Z. (2007)
Several maize near-isogenic inbred lines were subjected to comparative proteomics to identify kernel proteins associated with resistance. These lines were developed in Nigeria through a joint project between ARS-SRRC and the International Institute of Tropical Agriculture. The goal of this project is to develop aflatoxin-resistant inbreds for use in Central and West African national programs and U.S. breeding programs to combat aflatoxincontamination of maize. Parental lines that produced these inbreds were U.S. aflatoxin-resistant lines crossed with Central and West African lines selected for moderate to high ear rot resistance. Lines were selfed and selected for foliar and ear rot resistances and for good agronomic characteristics until the S4 generation where selection began for aflatoxin accumulation using a laboratory-based kernel screening assay (KSA) and field trials. Recently, inbred lines developed through the above-protocol were re-examined with the KSA and near-isogenic lines varying significantly in aflatoxin accumulation were identified. These lines were subjected to comparative proteomics and differences in protein expression between these near-isogenics were identified and results are discussed.